Respuesta :

Answer:

false

Step-by-step explanation:

hello

if f and g are inverse then (fog)(n)=n

as (fog)(n) is different from n it is false

hope this helps

Option B, false is right as g(n) is not the inverse of f(n).

What is an Inverse Function?

To find the inverse of a function the x in the function of f( x,y) is replaced by y and then the equation is solved for y, The function obtained is the inverse of the given function.

The function f(n) = -(n+1)³

it can be written in terms of y and n

y = - (n+1)³

The inverse of the function will be

n = -(y+1)³

[tex]\rm (y+1)^3 = -n\\\\\\y+1 = (-n)^{1/3}\\\\\\y = -1 -n^{1/3}[/tex]

this does not match the g(n).

Therefore, the option False is right as g(n) is not the inverse of f(n).

To know more about Inverse Function

https://brainly.com/question/2541698

#SPJ2